How much do range of movement and coordination affect Paralympic sprint performance? - Connick, M. J.; Beckmann, E.; Spathis, J.; Deubele, R.; Tweedy, S. M. (Medicine & Science in Sports & Exercise, 2015)
Introduction: Development of evidence-based methods of paralympic classification requires research quantifying the relative strength of association between ratio-scaled measures of impairment and sports performance. To date, no such research has been conducted. The purpose of this study was to quantify the extent to which range of movement (ROM) and coordination affect running performance in runners with and without brain impairment.